A Comparative Study of the Implementation of Sustainable Forest Management Policies in China and Indonesia: Lessons from Forest Management Practices - Wijaya Halim, Hadi (International Journal of Environmental Communication (ENVICOMM), 2025)
Sustainably preserving the functions of forests is the aim of sustainable forest management (SFM), which considers social, economic, and environmental issues.  For the sake of present and future generations, the FAO defines SFM as a dynamic concept that "aims to maintain and enhance the economic, social, and environmental values of all types of forests."  Enhancing livelihoods, maintaining biodiversity, preserving clean air and water, and lessening the consequences of climate change are just a few of the numerous benefits that sustainably managed forests may offer to both people and the environment. Two major players in the global climate change agenda are China and Indonesia, both of which have sizable forest areas. Indonesia, home to the biggest tropical peatland and third-largest tropical rainforest in the world, has seen a sharp rise in deforestation in recent decades. However, via government programs like the Grain for Green program, which reforests damaged land into wooded areas, China has accomplished a great deal of reforestation. A comparison of the two countries' forest management legislation is required in order to assess the effectiveness of different tactics and draw conclusions for sustainable forest governance. This article will examine the concept of SFM, examine the effectiveness of forest management policies in China and Indonesia, and evaluate the lessons learnt from them using the most recent statistics and official papers from sources such as the FAO, UNEP, the World Bank, and the relevant government publications. In addition to evaluating forest management strategies, this study looks at how environmental communication—particularly social media activism—influences public support for SFM programs.